2001
DOI: 10.1046/j.0960-7692.2001.00507.x
|View full text |Cite
|
Sign up to set email alerts
|

First‐trimester sonographic umbilical cord diameter and the growth of the human embryo

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…In human fetus, umbilical cord diameter (r=0.78), crownrump length (r=0.75) and biparietal diameter (r=0.81) were significantly correlated with gestational age [6]. Similar with these human results, umbilical cord (r=0.7074) and vein (r=0.7892) diameter were also significantly correlated with gestational age in Korean black goat.…”
Section: Discussionsupporting
confidence: 77%
“…In human fetus, umbilical cord diameter (r=0.78), crownrump length (r=0.75) and biparietal diameter (r=0.81) were significantly correlated with gestational age [6]. Similar with these human results, umbilical cord (r=0.7074) and vein (r=0.7892) diameter were also significantly correlated with gestational age in Korean black goat.…”
Section: Discussionsupporting
confidence: 77%
“…Of note, it has been reported that morphometric alterations of the umbilical cord in the first trimester of gestation are frequently seen in cases that subsequently develop preeclampsia or early fetal demise. 8 In conclusion, the present study shows that an association exists between the reduction of the umbilical vein cross-sectional area in late gestation and adverse neonatal outcome or fetal death. The temporal relationship between the sonographic changes in the umbilical cord and vessel areas and the occurrence of complications of pregnancy and adverse neonatal outcome remains to be explored.…”
Section: Resultsmentioning
confidence: 87%
“…[3][4][5][6][7][8] It has been demonstrated that a lean umbilical cord is associated with growth developmental disorders, 3 preeclampsia, 4 oligohydramnios, 3,7 and fetal distress during labor. 3,7 Correspondence to: F. Ghezzi A thin umbilical cord might be determined by a reduction of the amount of Wharton's jelly, as suggested by Schumann 1 and Hall, 2 by a reduction of the umbilical cord vessels' cross-sectional area, or by both.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that starting from the first trimester there is an association between umbilical cord diameter and anthropometric parameters. In a study by Ghezzi et al [14], umbilical cord diameter, crown-rump length, and biparietal diameter were measured in 439 fetuses at between 8 and 15 weeks of gestation. They found that umbilical cord diameter increased steadily as gestation advanced, and a significant correlation was found between umbilical cord diameter and gestational age, umbilical cord diameter and crown-rump length, and umbilical cord diameter and biparietal diameter.…”
Section: Discussionmentioning
confidence: 99%